International Textbook of Diabetes Mellitus 2003
DOI: 10.1002/0470862092.d0502
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Human Obesity

Abstract: This chapter summarizes the research on the role of genetic variation in human obesity. It provides a brief review of our current understanding of the level of heritability and of the familial risk for increasing levels of excess body weight. Single‐gene defects known to cause obesity are discussed. The results of a large number of association studies performed with candidate genes are described. The candidate genes with at least five positive studies are highlighted. All published genomic scan studies relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 259 publications
0
13
0
Order By: Relevance
“…We know, for example, that genes can affect each component of energy balance 45 and can explain some of the differences between individuals in body weight and body composition. While we can conclude that our genes are permissive for weight gain, the gradual weight gain of the population does not seem to be primarily due to genetic factors.…”
Section: How Did the Epidemic Arise?mentioning
confidence: 99%
“…We know, for example, that genes can affect each component of energy balance 45 and can explain some of the differences between individuals in body weight and body composition. While we can conclude that our genes are permissive for weight gain, the gradual weight gain of the population does not seem to be primarily due to genetic factors.…”
Section: How Did the Epidemic Arise?mentioning
confidence: 99%
“…Since the first study from QFS showing that there was no evidence of association between the A, B and C loci of the HLA system and various body fatness and fat distribution traits [23], a good number of association and linkage studies have been undertaken using data from QFS. It is beyond the scope of this report to review all these findings but such reviews can be found elsewhere [24–26]. Since linkage studies require family data, the primary contribution of our cohort to the identification of genes related to obesity came from genome-wide linkage studies.…”
Section: Role Of Genetics In the Etiology Of Obesitymentioning
confidence: 99%
“…According to the definition of the World Health Organization (WHO), approximately 6–10% of the population in Westernized countries is considered obese [3]. Epidemiological studies have shown that between 30–70% of the variation in body weight may be attributable to genetic factors [4]. Obesity related traits, such as body mass index (BMI), are influenced by both genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…BMI is an easy, reliable, accurate measurement and is highly correlated (0.8–0.9) with total fat mass in adults [5]. A number of studies have estimated the heritability of BMI to be 40%-55% [4,6], but estimates greater than 80% have been found in twin studies.…”
Section: Introductionmentioning
confidence: 99%